2018
DOI: 10.3390/ijms19103024
|View full text |Cite
|
Sign up to set email alerts
|

Non-Canonical Regulation of Type I Collagen through Promoter Binding of SOX2 and Its Contribution to Ameliorating Pulmonary Fibrosis by Butylidenephthalide

Abstract: Pulmonary fibrosis is a fatal respiratory disease that gradually leads to dyspnea, mainly accompanied by excessive collagen production in the fibroblast and myofibroblast through mechanisms such as abnormal alveolar epithelial cells remodeling and stimulation of the extracellular matrix (ECM). Our results show that a small molecule, butylidenephthalide (BP), reduces type I collagen (COL1) expression in Transforming Growth Factor beta (TGF-β)-induced lung fibroblast without altering downstream pathways of TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Further supporting this, we find here a significant increase of differentiating SOX2-positive club cells with aging, which again was anticipated in the telomerase-deficient mice. Sox2 has been previously shown a marker of differentiation of club cells ( Tompkins et al, 2009 ), which is increased in bleomycin-induced pulmonary fibrosis in mice ( Chuang et al, 2018 ), as well as in patients suffering from IPF ( Plantier et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting this, we find here a significant increase of differentiating SOX2-positive club cells with aging, which again was anticipated in the telomerase-deficient mice. Sox2 has been previously shown a marker of differentiation of club cells ( Tompkins et al, 2009 ), which is increased in bleomycin-induced pulmonary fibrosis in mice ( Chuang et al, 2018 ), as well as in patients suffering from IPF ( Plantier et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The There are examples shows the crucial role of these peptides in human genes. In 2019 Szpiech and colleagues suggested that Runs of homozygosity (ROH) 'are associated with an inflation of deleterious homozygous variation [20]. They have suggested that ' African haplotype backgrounds may play a particularly important role in the genetic architecture of complex diseases [21].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, ZNF678 , which is involved in transcriptional regulation, interacted with EPB41L3 in the STRING protein–protein interaction network analysis ( Figure S8 ). Among the 99 proteins interacting with ZNF687, 33 proteins, including MYC [ 29 ], CSNK2A1 [ 30 ], CDKN2A [ 31 ], HDAC2 [ 32 ], MI1 [ 33 ], SOX2 [ 34 ], and RNF2 [ 35 ], have been revealed to be associated with fibrosis. These data indicate that EPB41L3 may be regulated through interactions with ZNF687 and interacting genes.…”
Section: Discussionmentioning
confidence: 99%